2021
DOI: 10.1111/jvs.13014
|View full text |Cite
|
Sign up to set email alerts
|

Alien plant invasion hotspots and invasion debt in European woodlands

Abstract: Questions: European woodlands harbor at least 386 alien plant species but the factors driving local invasions remain unknown. By using a large vegetation-plot database, we asked how local richness and abundance of alien species vary by regions, elevation, climate, soil properties, human disturbance, and habitat types.Location: Western, central and southern Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 56 publications
(104 reference statements)
1
21
0
1
Order By: Relevance
“…The present research shows that invasive trees were more likely to be introduced, become established, and spread in tropical or subtropical areas [ 5 ]. Most of these 11 invasive tree species are native to tropical and subtropical areas of South America, southern Europe, East Asia, and South Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present research shows that invasive trees were more likely to be introduced, become established, and spread in tropical or subtropical areas [ 5 ]. Most of these 11 invasive tree species are native to tropical and subtropical areas of South America, southern Europe, East Asia, and South Asia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hiptage benghalensis is a weed in the tropical rain forests of Australia and is highly invasive to Mauritius and Réunion, where it thrives in the dry lowland forests forming impenetrable stands of shrubs and suffocating the local vegetation [ 5 , 6 , 7 ]. Other studies have shown that some species may invade only a limited area but are likely to expand and cause further substantial damage [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 15 contributions used fine‐grain plant community data to address macroecological questions at various extents: global (Kusumoto et al, 2021; Testolin et al, 2021), across the whole Palaearctic (Biurrun et al, 2021; Dembicz et al, 2021; Zhang et al, 2021), across Europe (Axmanová et al, 2021; Boonman et al, 2021; Padullés Cubino et al, 2021; Sporbert et al, 2021; Večera et al, 2021), larger parts of Europe (Cao Pinna et al, 2021; Wagner et al, 2021) or at state level (Bourgeois et al, 2021; Craven et al, 2021). Most of these studies rely on two large vegetation‐plot databases established and maintained by two working groups of the International Association for Vegetation Science (IAVS), the European Vegetation Archive (EVA; Chytrý et al, 2016) by the European Vegetation Survey (Axmanová et al, 2021; Boonman et al, 2021; Cao Pinna et al, 2021; Padullés Cubino et al, 2021; Sporbert et al, 2021; Večera et al, 2021; Wagner et al, 2021) and the GrassPlot database (Dengler et al, 2018) by the Eurasian Dry Grassland Group (Biurrun et al, 2021; Dembicz et al, 2021; Zhang et al, 2021). Testolin et al (2021) used data from the global vegetation‐plot database sPlot (Bruelheide et al, 2019), and four relied on regional data compilations (Bourgeois et al, 2021; Craven et al, 2021; Kusumoto et al, 2021; Tordoni et al, 2021).…”
Section: Contributions In the Special Issuementioning
confidence: 99%
“…The storage and reuse of these data is now a fundamental source of information to address ecological and biogeographical questions, such as vegetation and habitat classification, ecological modeling, plant species invasions, understanding biodiversity patterns from a macroecological perspective or testing island biogeography theory (Chytrý et al 2020;Biurrun et al 2021;Chiarucci et al 2021;Wagner et al 2021). The large amount of available vegetation plots estimated for Europe by Schaminée et al (2009) underlines the great potential offered by these data and, therefore, the necessity of make them easily available.…”
Section: Introductionmentioning
confidence: 99%